2023
DOI: 10.3390/antibiotics12050845
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Essential Oil from Lippia origanoides on the Transcriptional Expression of Genes Related to Quorum Sensing, Biofilm Formation, and Virulence of Escherichia coli and Staphylococcus aureus

Abstract: Microbial infections resistant to conventional antibiotics constitute one of the most important causes of mortality in the world. In some bacterial species, such as Escherichia coli and Staphylococcus aureus pathogens, biofilm formation can favor their antimicrobial resistance. These biofilm-forming bacteria produce a compact and protective matrix, allowing their adherence and colonization to different surfaces, and contributing to resistance, recurrence, and chronicity of the infections. Therefore, different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Therefore, anti-virulence therapy through blocking virulence factors or virulence-associated processes has been shown to be a new alternative therapeutic strategy for bacterial infection. Numerous studies indicated that some plant-derived bioactive compounds were able to control bacterial infection via targeting virulence factors ( Liu et al., 2020 ; Hou et al., 2023 ; Martínez et al., 2023 ). It is found that tectorigenin, an isoflavone extracted from the rhizome of the Chinese herb Belamcanda chinensis (L.) DC, displayed no observable antibacterial activity against C. perfringens , but it significantly inhibited the gliding motility, biofilm formation and adherence to Caco-2 cells of the bacteria by suppressing type IV pilus-associated genes expression ( Liu et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, anti-virulence therapy through blocking virulence factors or virulence-associated processes has been shown to be a new alternative therapeutic strategy for bacterial infection. Numerous studies indicated that some plant-derived bioactive compounds were able to control bacterial infection via targeting virulence factors ( Liu et al., 2020 ; Hou et al., 2023 ; Martínez et al., 2023 ). It is found that tectorigenin, an isoflavone extracted from the rhizome of the Chinese herb Belamcanda chinensis (L.) DC, displayed no observable antibacterial activity against C. perfringens , but it significantly inhibited the gliding motility, biofilm formation and adherence to Caco-2 cells of the bacteria by suppressing type IV pilus-associated genes expression ( Liu et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies indicated that some plant-derived bioactive compounds were able to control bacterial infection via targeting virulence factors and slow down the rise of resistant strains ( Liu et al., 2020 ; Hou et al., 2023 ; Martínez et al., 2023 ). Baicalin-aluminum is a complex of aluminum and baicalin.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of the structural components of curli genes, including the csgD gene, was drastically reduced in the presence of caffeine, starting from the lowest concentration of 20 mM. The essential oil of Lippia origanoides thymol-Carvacrol II chemotype also demonstrated biological activity against E. coli ATCC 25992 [57]. This essential oil was found to inhibit biofilm formation by downregulating the expression of genes involved in cell aggregation (csgD gene) in E coli.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the decrease in PGA, obtained by treating the bacteria with the mixtures, caused the instability of the biofilm, with the loss of its architecture. PGA is an essential protein for maintaining the structural integrity of the biofilm, and the downregulation of the pga genes hinders its formation [53,54].…”
Section: Gene Expression Analysismentioning
confidence: 99%